GAMBARAN PERTUMBUHAN PADA ANAK USIA PRASEKOLAH DI BEE STAR WONOSOBO - Indriani, Farihah; Setyawati, Ari; Tyarini, Indrawati Aris; Resmi, Dewi Candra (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2023)
Pupose of the research is to describe the growth of preschool children at Bee Star Wonosobo. The growth process is assessed by anthropometric examination including body weight and height. The factor that most influences growth is nutritional status. Good nutritional intake to fulfill children's physical and mental needs greatly influences brain growth and development and the development of other organs. Method used descriptive quantitative, which was carried out using accidental sampling, and obtained a sample of 55 children with the sample criteria being children aged 3-6 years and willing to have anthropometric measurements taken. Research data was obtained from anthropometric measurements including height, weight and body mass index, then the data was subjected to descriptive analysis. Results of anthropometric measurements in this study showed that respondents had a normal height namely 24 (66.67%), were overweight namely 16 (44.44%) and had an excess BMI (body mass index) namely 19 (52.78%). Conclusion is that there are children who have insufficient height, excessive body weight and excessive body mass index.